Clinical Decision Support Enhanced by User Acceptance Testing to Promote Situational Awareness for Pediatric Patients with a Difficult Airway - Dahl, Megan; Thompson, Sarah; Chih, Jerry; Kandaswamy, Swaminathan; Orenstein, Evan; Long, Justin B. (Applied Clinical Informatics, 2025)
Children with a difficult airway are at high risk of decompensation in the setting of respiratory distress. Situational awareness among all team members, and a shared plan in case of an emergency, can reduce the chance of catastrophic outcomes.This study aimed to improve difficult airway situational awareness while minimizing alert burden in a quaternary care pediatric healthcare system through the application of clinical decision support (CDS).Three iterative designs were developed and implemented from 2015 through 2023. We measured interruptive alert burden and performed observations between each implementation to estimate point prevalence among hospitalized patients with a difficult airway of three desired behaviors: presence of a difficult airway sign at the head of the bed, orders placed for appropriate equipment nearby, and primary nurse awareness of the difficult airway.Over the course of the redesign, the alert burden decreased from 12,316 firings per month to 125 firings per month from the first alert to the second redesign and final iteration. There was a statistically significant increase in the proportion of difficult airway patients with orders for appropriate equipment from 51.4 to 83.9% (p < 0.001). There was no significant change in difficult airway sign placement (71.4–87.1%, p = 0.29) or observed nurse awareness of difficult airway status of the patient (80.0–87.1%, p = 0.447). The greatest improvements in alert burden and rates of desired user action occurred after redesigning based on usability testing.CDS redesign using popular frameworks alone reduced alert burden without significantly worsening situational awareness. Redesign through guerilla in situ usability testing led to much more substantial reductions in alert burden and greater improvements in desired user action.
Keywords: decision support systems; clinical awareness; user-centered design; alert fatigue; health personnel